Preventing child abuse and neglect in Romania - Enache, Rodica Gabriela; Mihai, Radu (Technium Social Sciences Journal, 2021)
In this paper we analyze the phenomenon of abuse and neglect in Romania in order to reduce the incidence of this phenomenon. This paper addresses issues regarding: the description of child abuse, types of child abuse (e.g.: physical abuse; sexual abuse; emotional / psychological abuse and child neglect), particularities of children abuse in Romania, and some therapeutic models used in treating the effects of child abuse.